The Science of Creating Brand Associations: A Continuous Trinity Model Linking Brand Associations to Learning Processes - du Plessis, Christilene; D’Hooge, Serena; Sweldens, Steven (Journal of Consumer Research, 2024)
Abstract The continuous trinity model (CTM) of brand associations integrates 50 years of consumer learning research with recent conceptualizations of consciousness. Three types of brand associations are proposed at the representational level (expectations, meaning, and affect), corresponding to three types of learning at the process level (predictive learning, referential learning, and direct affect transfer). A core proposition derived from research on automaticity holds that the operating conditions of the learning processes vary on a continuum from mostly System 2 for predictive learning to mostly System 1 for direct affect transfer, with referential learning as a mix of the two. The CTM aims to bring clarity and structure to a complex literature by highlighting the web of interrelations between operating principles (“what” brand associations are learned), operating processes (“how” brand associations are learned), and operating conditions (“when” brand associations are learned). For consumer and learning researchers, the CTM outlines an agenda for future research and guidelines to improve conceptual and methodological clarity. For brand managers, the CTM provides tactical recommendations (a “toolkit”) for structuring advertising campaigns to create desired brand associations and strategic recommendations for managing brand partnerships. For policymakers, the CTM offers guidance on types of advertisements requiring closer scrutiny.